Analysis of the role of M-type hexaferrite-based materials in electromagnetic interference shielding - Mathews, Shalom Ann; Babu, D. Rajan (Current applied physics, 2021)
M-type hexaferrite has attracted much attention for its large magneto-crystalline anisotropic energy, exceptionally good chemical stability, corrosion resistance, high Curie temperature, and high coercivity. In this review paper, our goal is to examine the microwave absorption properties and related studies of M-type hexaferrite-based materials. The microwave absorption properties of hexaferrite-based materials in the S, X, and Ku-band are discussed with their corresponding reflection losses. Complementarity between magnetic loss and dielectric loss is found to have a great impact on the proper absorption of microwaves. The mechanisms corresponding to the microwave absorption in different morphologies and structural adaptations of hexaferrite have been elaborated in the article. The ongoing trends and future perspectives of these materials are also outlined. [Display omitted] •Recent investigations into M-type hexaferrites have been discussed.•The need for electromagnetic wave shielding material is addressed.•Basic mechanisms involved in shielding electromagnetic radiations are explained.•Role of M-type hexaferrite based materials in shielding the radiations are detailed.•Future prospective of the effective shielding materials in trend are viewed.